Blockchain Scalability Analysis and Improvement of Bitcoin Network through Enhanced Transaction Adjournment Techniques - Maiwada, Umar Danjuma (Wasit Journal of Computer and Mathematics Science, 2025)
Bitcoin is the most popular among the cryptocurrency it includes Litecoin, Dogecoin, and Peercoin. Blockchain is the foundation of cryptocurrencies, most cryptocurrency technologies are decentralized. Despite its benefits, blockchain remains a cutting-edge technology with flaws that can be addressed to increase efficiency. Therefore, this research digs into the topic of scalability in blockchains and presents a comparative analysis of numerous blockchain metrics with real time data. We performed this using a blockchain simulation (BlockSim), and then looked at effective techniques that may be utilized to overcome the limitation by comparing the simulator and real-world circumstances. The second part of this research work proposes an effective algorithm that improves scalability of Bitcoin network through efficient transaction deferment. In this study, we propose an algorithm that improves the current Bitcoin protocols using Inventory messaging (INV) and transaction deferment or adjournment. The deferred transaction relay on the message to carry multiple raw transactions. These improvements are compatible with the existing Bitcoin Network protocols. The improve algorithm was simulated using BlockSim and AnyLogic Multi Paradigm Simulation Engine, the simulators ware configured with 1000 nodes interconnected in a Bitcoin Like Peer-to-Peer network. The result of the simulation shows that the adjourned transaction protocol provides for a controlled reduction in the number of messages required to propagate a transaction at the cost of a modest increase in transaction propagation time. We may manage the tradeoff between the quantity of messages and propagation latency by adjusting the threshold and timeout values, thereby improving the network’s overall scalability. Bitcoin is the most popular among the cryptocurrency it includes Litecoin, Dogecoin, and Peercoin. Blockchain is the foundation of cryptocurrencies, most cryptocurrency technologies are decentralized. Despite its benefits, blockchain remains a cutting-edge technology with flaws that can be addressed to increase efficiency. Therefore, this research digs into the topic of scalability in blockchains and presents a comparative analysis of numerous blockchain metrics with real time data. We performed this using a blockchain simulation (BlockSim), and then looked at effective techniques that may be utilized to overcome the limitation by comparing the simulator and real-world circumstances. The second part of this research work proposes an effective algorithm that improves scalability of Bitcoin network through efficient transaction deferment. In this study, we propose an algorithm that improves the current Bitcoin protocols using Inventory messaging (INV) and transaction deferment or adjournment. The deferred transaction relay on the message to carry multiple raw transactions. These improvements are compatible with the existing Bitcoin Network protocols. The improve algorithm was simulated using BlockSim and AnyLogic Multi Paradigm Simulation Engine, the simulators ware configured with 1000 nodes interconnected in a Bitcoin Like Peer-to-Peer network. The result of the simulation shows that the adjourned transaction protocol provides for a controlled reduction in the number of messages required to propagate a transaction at the cost of a modest increase in transaction propagation time. We may manage the tradeoff between the quantity of messages and propagation latency by adjusting the threshold and timeout values, thereby improving the network’s overall scalability.